Type D or “distressed” personality in sarcoidosis and idiopathic pulmonary fibrosis - Elfferich, M.D.P.; De Vries, J.; Drent, M. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2011)
Background: Personality factors have shown to be related to mortality, morbidity, and psychological aspects in chronic disorders. Little is known about the effect of personality on disease severity in sarcoidosis and idiopathic pulmonary fibrosis (IPF). The aim of this study was to assess the prevalence of Type D personality and its relation with relevant clinical characteristics in sarcoidosis and IPF patients. Methods: The study included 441 sarcoidosis and 49 IPF patients from the outpatient clinic of the ild care team of the MUMC, the Netherlands.They completed the DS14 (Type D questionnaire), the fatigue assessment scale (FAS), theWHO quality of life-BREF (WHOQOL-BREF) and the Centre for Epidemiological Studies-Depression Scale (CES-D).Moreover, relevant clinical data were collected. The control group consisted of 3678 subjects from a general population. Results: Type D personality was found in 25.6% of the sarcoidosis patients compared to 21% in the controls, but only in 18.8% of the IPF patients. No relation with disease severity was found in either of these disorders. Fatigue was a substantial problem in both populations. Depressive symptoms but not Type D personality predicted fatigue and poorer QOL in sarcoidosis and IPF. Conclusion: Prevalence of Type D personality is not higher in sarcoidosis and IPF patients than in the general population and does not explain QOL impairment. Depressive symptoms explain QOL impairment and fatigue substantially. Therefore, in the multidisciplinary management of sarcoidosis and IPF psychological screening and psychological counselling concerning adequate coping strategies should be incorporated.